(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Narratology refers a discipline of humanities which is devoted to the study of the logic, principles and customs of narrative representation. Narratology denotes not only theory and the study of narrative but also narrative structure and the distinctive ways that these affect our perception. Being a multicultural country, India possesses numerous style of storytelling. While some narrate, other use props like masks, puppet etc. And few narrate story through dance music. Raja Rao portrayed ‘Katha’ an Indian style of religious storytelling in the novel Kanthapura. This article attempts to exhibit the narrative elements and techniques used by Raja Rao through his significant novel Kanthapura. Further this article throws light on the facets of Narratology in the select novels of Chetan Bhagat. In Kanthapura, Raja Rao distinctively employed religious metaphor as a narrative technique by keeping in tone and content of the novel. The narrator of the novel, shrewdly mingles the past with the present and by means of the religious metaphor she explains the subtleties of freedom movement. In Kanthapura, he depicted witness narrator vividly. Chetan Bhagat employed innovative narrative technique such as news, diary entries, scrapbook, transcripts, telephonic conversation, speech sessions, SMS, e-mails, epilogues and prologues etc. Chetan Bhagat employs technological devices and methods in his story-telling which attracts numerous readers.